CpG Oligodeoxynucleotides for Anticancer Monotherapy from Preclinical Stages to Clinical Trials - Zhongkun Zhang; Jimmy Chun-Tien Kuo; Siyu Yao; Chi Zhang; Hira Khan; Robert J. Lee (MDPI AG, 2021)
CpG oligodeoxynucleotides (CpG ODNs), the artificial versions of unmethylated CpG motifs that were originally discovered in bacterial DNA, are demonstrated not only as potent immunoadjuvants but also as anticancer agents by triggering toll-like receptor 9 (TLR9) activation in immune cells. TLR9 activation triggered by CpG ODN has been shown to activate plasmacytoid dendritic cells (pDCs) and cytotoxic T lymphocytes (CTLs), enhancing T cell-mediated antitumor immunity. However, the extent of antitumor immunity carried by TLR agonists has not been optimized individually or in combinations with cancer vaccines, resulting in a decreased preference for TLR agonists as adjuvants in clinical trials. Although various combination therapies involving CpG ODNs have been applied in clinical trials, none of the CpG ODN-based drugs have been approved by the FDA, owing to the short half-life of CpG ODNs in serum that leads to low activation of natural killer cells (NK cells) and CTLs, along with increases of pro-inflammatory cytokine productions. This review summarized the current innovation on CpG ODNs that are under clinical investigation and explored the future direction for CpG ODN-based nanomedicine as an anticancer monotherapy.